2019
DOI: 10.1186/s12877-019-1148-5
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition risks and their associated factors among home-living older Chinese adults in Hong Kong: hidden problems in an affluent Chinese community

Abstract: Background Although China is undergoing rapid economic development, it is facing an ageing population. No data exists on malnutrition risks of older adults in an affluent Chinese society. The aim of this study is to examine these risks and identify their associated factors among home-living older Chinese adults in Hong Kong. Methods This is a cross-sectional study, to which home-living subjects aged 60 or above were recruited, between May and September 2017, from a non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 57 publications
2
25
2
Order By: Relevance
“…Although breakfast skipping is less studied in older adults, evidence in their younger counterparts offers insight about what to expect. For example, breakfast skipping was associated with lower skeletal muscle mass in young adults [ 37 ], which seems feasible in older adults because meal skipping might lead to malnutrition [ 38 ] and skeletal muscle loss [ 39 ]. Additionally, breakfast skipping is associated with a higher risk of developing type 2 diabetes in adults of different ages (18–83 year) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although breakfast skipping is less studied in older adults, evidence in their younger counterparts offers insight about what to expect. For example, breakfast skipping was associated with lower skeletal muscle mass in young adults [ 37 ], which seems feasible in older adults because meal skipping might lead to malnutrition [ 38 ] and skeletal muscle loss [ 39 ]. Additionally, breakfast skipping is associated with a higher risk of developing type 2 diabetes in adults of different ages (18–83 year) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This tool has a depression diagnostic performance and acceptable reliability that are similar to those of the original 30‐item Geriatric Depression Scale (area under the curve: 0.77; sensitivity: 0.64; specificity: 0.79 to clinical diagnosis; Cronbach's α: 0.77) among older Chinese population in Hong Kong 7 . The covariates included sociodemographics, lifestyle characteristics, health status, and dietary factors 2 . The association between malnutrition and depression risks was examined by using multivariable logistic regression in a hierarchical fashion after adjustment for the covariates.…”
Section: Step 1 or (95%ci) P‐value Step 2 Or (95%ci) P‐value Step 3 Omentioning
confidence: 99%
“…This was a cross‐sectional survey of 610 older adults (mean age: 78.5 ± 7.4 years, 53.8% women) living alone or with only a spouse in Hong Kong. The survey's methodology is described elsewhere 2 . A sample size of 600 participants was presumed to be adequate to estimate the prevalence of malnutrition and depression risks, with a margin of error no greater than ±4% at a 5% level of significance.…”
Section: Step 1 or (95%ci) P‐value Step 2 Or (95%ci) P‐value Step 3 Omentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of undernutrition among older people living in the community ranges between 1.3% and 47.8% and is much higher in low and middleincome countries . Studies done in countries like China showed 30% at risk of Malnutrition (Wong et al, 2019) and in Nepal, 49.6% were at risk for malnutrition while 24.8% were in the malnourished range, based on Mini Nutritional Assessment scores (Tamang et al, 2019;Parasuraman and Raveendran, 2011). Hospital-based Norway study associates sarcopenia, cancer and pulmonary disease with the declining nutritional status (Jacobsen et al, 2016).…”
Section: Factors Associated With Malnutritionmentioning
confidence: 99%